Intention Toward Entrepreneurship : The Case of Libyan Master's Students in Universiti Utara Malaysia and Garyounis University - Aneizi, Ibrahim Othman (2009)
The main objective of this study is to determine whether there is difference in the intention toward entrepreneurship between Libyan male students studying in University Utara Malaysia (UUM) and Garyounis University (GU). In order to measure that, three dimensions of entrepreneurship which are attitude toward behavior, subjective norms, and perceived behavior control were used. Data were gathered through questionnaire survey of 120 Libyan male masters student studying under College of Business in UUM (n=28) and GU (n=92). Correlation, independent group t-test, and regression analysis were used to examine the relationship, the differences between the variables and the extent of contribution of the variables to entrepreneurship intention. The result indicated that the level attitude towards behavior, subjective norms, and perceived behavior control and intention toward entrepreneurship for UUM’s students is higher than GU's students.UUM being the university that stress an exposure to entrepreneurship environment (formal and informal education) shows higher intention toward entrepreneurship compared to those in GU who are not exposed to entrepreneurship environment.